Students’ Perception of Informal Assessment in the English Classroom At MYLIBERTY - Muh Nofal Lakasim; Sartin T. Miolo; Haris Danial (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate students’ perceptions of informal assessment in the English classroom at MYLIBERTY in a mixed-age learning environment. This study used a descriptive quantitative design with one variable, namely students’ perceptions of informal assessment. The participants were 20 students selected through purposive sampling. The instrument was a questionnaire with 24 Likert-scale statements based on Robbins’ theory of perception (1996) and Brown’s concept of informal assessment (2004). Data were analyzed using descriptive statistics, including frequency, percentage, and mean score. The results show that students have a very positive perception of informal assessment in all dimensions, namely perceiver factors, object factors, and situational context factors. The highest result was found in perceiver factors, especially motivation and attitude, showing that students feel more confident and motivated during informal assessment activities. Object factors such as assessment types, clarity of instructions, and novelty were also rated positively, indicating that informal assessment is considered clear, varied, and interesting. In situational context factors, students also responded positively to time allocation, classroom conditions, and social interaction, which support a comfortable learning environment. Overall, informal assessment helps increase students’ participation, confidence, and engagement in learning English. In conclusion, informal assessment gives a positive impact on students’ learning experience in mixed-age classrooms.